Proteoglycans in articular cartilage revealed with a quick freezing and deep etching method. Issue 7 (July 1996) - Toriumi, H; Nakagawa, H; Ueda, H; Leng, C G; Fujii, Y; Ohno, S
Abstract : OBJECTIVES: To clarify the three dimensional ultrastructure of proteoglycans, and their relationship with other matrix components in articular cartilage. METHODS: Specimens from rat femoral heads were examined using three techniques: (1) Histochemical staining with cationic polyethyleneimine (PEI), using a pre-embedding or a postembedding method. Some tissues were pretreated with chondroitinase ABC or hyaluronidase. (2) Quick freezing and deep etching (QF-DE). Some specimens were fixed with paraformaldehyde and washed in buffer solution before quick freezing; others were frozen directly. (3) Ultrathin sections were studied after conventional preparation. RESULTS: Proteoglycans were observed as aggregated clumps with PEI staining by the pre-embedding method, but as fine filaments by the postembedding method. They were lost with enzyme digestion; this was also demonstrated by the QF-DE method. The ultrastructure was well preserved by the QF-DE method when fixation and washing procedures were included, but not without these procedures. A fine mesh-like structure was connected to the cell membrane in the pericellular matrix. Filamentous structures suggestive of aggrecans were observed among collagen fibrils. They had side chains, approximately 50 nm in length, which branched from the central filaments at intervals of 10-20 nm, and were occasionally linked to other structures. Many thin filaments were also attached to the collagen fibrils. CONCLUSIONS: The QF-DE method incorporating paraformaldehyde fixation and buffer washing procedures revealed three dimensional, extended structures suggestive of proteoglycans.